PENGARUH LINDI HASIL BIOKONVERSI SAMPAH BUAH OLEH LARVA BLACK SOLDIER FLY (Hermetia illucens (L)) TERHADAP NILAI EDAFIK, KANDUNGAN NPK, MIKROORGANISME, DAN PERTUMBUHAN SELADA BUTTERHEAD (Lactuca sativa var. capitata) DALAM SISTEM HIDROPONIK NUTRIENT FILM TECHNIQUE (NFT) - Rafifin, Nabil
Food needs such as vegetables are increasing, but agricultural land is decreasing, in other hand the problem of the volume of garbage is increasing. The solution that can be offered is to use a hydroponic system and use an organic nutrient solution from the process of bioconversion of fruit waste with the Black Soldier Fly (Hermetia ilucens) agent, so that the volume of waste in urban areas can be reduced. Butterhead lettuce has a soft leaf texture, so it is preferred by consumers. The aim of this study was to determine the condition of pH, dissolved oxygen (DO), and the amount of total dissolved solids (TDS) in a combination of leachate solution BSF with AB Mix that was optimal for the growth of butterhead lettuce (Lactuca sativa L. var. Capitata). Butterhead lettuce is grown using the NFT system with a 100% AB mix solution; AB mix 70% and leachate BSF 30%; AB mix 60% and leachate BSF 40%; AB mix 50% and BSF leachate 50%; AB mix 40% and BSF leachate 60%; Lindi BSF 100%. This study comparing edafic values and check the nutrient solution content, total microorganisms, wet and dry weight, fiber content, vitamin C, and total chlorophyll. If the leachate combination is reduced, the pH value will be more acidic, and the TDS value will increase. That is because BSF leachate is alkaline. AB Mix 60% and leachate 40% produce an average number of leaves 20 ± 4.7 strands; wet weight of 46.033 ± 14.27 grams; dry weight 2.04 ± 0.39 gram; total chlorophyll 6.126 ± 0.047 mg / L; total vitamin C 46.1 mg / 100g; and 0.95% fiber content based on the results of statistical tests conducted this treatment was not significantly different from the treatment of 100% AB Mix. PH value of 7.92; dissolved oxygen 7.56 mg / L; and dissolved solids of 580 ppm in the treatment of AB Mix 60% and Lindi 40% can be concluded as the best composition for the growth of butterhead lettuce by hydroponic NFT.